ENGLISH TEACHERS’ OF VOCATIONAL HIGH SCHOOL’S RESPONSE ON LITERACY STRATEGY IN 2013 CURRICULUM REVISION - Laila Nurul Faidah (The Ellite of Unira, 2020)
This research aims to describe the teachers’ understanding about literacy strategy in 2013 curriculum revision in Palengaan district This research design of this study is qualitative. This study focus on literacy strategy. The literacy can be defined as a set of cultivated skills and knowledge that serve as a basis for learning, communication, language use and social interaction. Literacy strategy (Directorate of guidance on vocational high school) is inseparable from education. Literacy becomes a means of learners in knowing, understanding, and applying the knowledge that is in school. Object of this study was that focus on response English teacher about literacy strategy, and took six samples of English teacher using interview and questionnaire. Based on the result of research it can conclude that from six subject of English teachers in vocational high school in Palengaan district has poor understanding, they ever heard about literacy strategy but they only said literacy strategy is one strategy from 2013 without knowing its essence. English teachers of vocational high school response in Palengaan district for literacy strategy in 2013 curriculum revision only two teachers give positive response because according to them the literacy strategy in 2013 curriculum is better than the previous curriculum, and four teachers give negative response because according to them literacy strategy is not effective and conducive in teaching-learning process.